EXPLORING THE LITERARY MERITS AND CONTROVERSIES OF 'FIFTY SHADES OF GREY' MOVIE IN CONTEMPORARY POPULAR CULTURE - Aristawidya, Syifa Kartika (Universitas Negeri Semarang, 2023)
This research delves into the literary merits and controversies surrounding the 'Fifty Shades of Grey' movie in contemporary popular culture. Through a comprehensive literature review, we explore the captivating narrative, thematic exploration, and character development that contribute to the film's literary merits. Additionally, we examine the controversies, which encompass its portrayal of BDSM, consent, unequal power dynamics, and treatment of abuse and trauma. The research methodology used is a literature review, which involves analyzing existing scholarly works, critical essays, and articles related to the 'Fifty Shades of Grey' movie. The 'Fifty Shades of Grey' movie exhibits literary merits in its engaging narrative, thematic exploration, and character development. However, it also faces controversies regarding its portrayal of BDSM and concerns about consent, power dynamics, and handling of abusive behavior. The film's cultural impact and discussions about relationships and sexuality mark its significance in contemporary popular culture.